Micro-foundations for Innovation Policy - Raad voor het Regeringsbeleid, Wetenschappelijke; Nooteboom, B.; Stam, E. (WRR Rapporten, 2008)
In economics, business, and government policy, innovation policy requires the creation of new approaches based on insight in what happens in innovation processes, on the micro level of people, firms and interaction between them. In innovation policy it should also be recognized that innovation entails a whole range of activities beyond R&D, such as entrepreneurship, design, commercialization, organization, collaboration and the diffusion of knowledge and innovations . This edited volume explores the roles of individuals and organizations involved in the creation and application of innovations. Covering topics as diverse as the macro-economic importance of innovation, theories of knowledge and learning, entrepreneurship, education and research, organizational innovation, networks and regional innovation systems, Micro-Foundations for Innovation Policy provides critical insights into the development of innovation policy. This title is available in the OAPEN Library - http://www.oapen.org.